MONITORING OF THE SPATIAL PARAMETERS OF RECLAIMED LAND BY MEANS OF AERIAL PHOTOGRAPHY - Mamonov К.; Kovalchuk В.; Horb О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
The study is devoted to the possibilities of aerial photography to identify inconsistencies between project solutions determined by the working project of land management for reclamation of disturbed lands and the actual conditions of the elements of reclamation on the ground at certain intervals. The supplied example shows the need to monitor the processes that occur after land reclamation. Modern technological solutions are offered to solve the problem. To determine the spatial parameters of the reclamation object, it is proposed to use aerial photography by unmanned aerial vehicles. Due to the exact reference to the geodetic network in different periods, it is possible to obtain a spatial model of the same area and use the obtained models to measure soil erosion, compliance with the project of technical measures for reclamation, effectiveness of the implemented biological reclamation, volume of the soil inwashing and outwashing, steepness of the slopes. In addition, the work describes visualization of the monitoring processes by means of various functions of specialized software, namely orthophoto plans, elevation maps, change of horizontals, and area of grass vegetation by observation cycles. By using three cycles of measurements with one-year interval, the reserchers determined volume of soil erosion and its dependence on the coverage of the ground's surface with grass vegetation. These parameters help to make decisions about efficiency of the land-reclamation work in combination with other methods of assessing soil conditions, and, if necessary, to correct the project solutions, as well as gain scientifically grounded experience for implementation in the following production projects.